The Impact of An Education Program upon Women’s Knowledge in Managing Breast Self–Examination - Abdullah, abla; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2010)
Objective: To find out if there are any significant differences between these women’s knowledge in the management of Breast Self-Examination in study and control group regarding some variables. Methodology: A quasi-experimental design was used. A purposive "non-probability" sample of (260) women who are employee and students in both colleges (Nursing and Health and Medical Technologies) was selected. The sample consists of two groups, experimental group (130) includes those in (Nursing college), and control group (130) in (Health and Medical Technologies). A questionnaire was constructed which included demographic information, reproductive information, family history, previous medical history, and information about women’s knowledge in managing breast-self examination (BSE). Data were collected through the use of the questionnaire, the application of the educational program. A post-test was done for the study only which uses the lectures, booklet, training practices of BSE, and video film. Data analysis was performed through the application of descriptive and inferential statistical approaches. Results: There are significant associations between women’s knowledge regarding managing BSE and their marital status, infertility status, lactation and second degree consanguinity; also the study concluded that the educational program of BSE is necessary for all women in different age groups, with different medical histories, educational level, occupational status, and considered as an effective mean for the reinforcement of improvement of women’s knowledge regarding managing BSE. Recommendations: Implementation of proposed model of continuous medical education for women for BSE within the scope of their work.